DIGITALISASI BAHAN AJAR UNTUK GURU SMK: DARI PELATIHAN KE TRANSFORMASI KELAS - Kusworo Kusworo; Sefrimel Angriani ZN; Ivan Putranto; Sintia Nursafitri; Prima Andriani; Bagus Kharismawan (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2025)
Technological developments in supporting the implementation of learning are a challenge in an effort to provide quality education services. Teachers must be able to adapt to technological developments through various innovations in learning, both related to strategies, methods and media that are integrated with technology in order to be able to meet the needs of students and answer the challenges of technological developments. However, not all teachers are able to quickly implement digital-based learning to meet these demands. This community service activity aims to strengthen the competence of teachers at SMK L'PINA East Jakarta through training on the preparation of digital teaching materials. The methods carried out in service activities are in the form of training, mentoring, and evaluation given to pre-teachers. The results of the service showed a change in the improvement of teacher competence before and after carrying out community service activities, which was 16%. This pre-training and post-training evaluation showed an increase in teachers' confidence and skills in making digital teaching materials. This activity has proven to be a positive contribution in supporting the role of dedicated lecturers to work together in improving the quality of education, especially improving the ability of teachers to provide digital-based teaching materials. Service activities held in the form of training and mentoring as well as continuous evaluation are able to be a catalyst for digital transformation in the school environment. This activity ultimately also strengthens collaboration between universities and partner schools in encouraging innovation in learning and teaching activities. Keywords: Digital Teaching Materials, Quality Of Education, Teacher Training, Educational Technology;.